Development of occupation from the therapeutic activity of yoga - Turner, Kristin M., author; Schmid, Arlene A., advisor; Hooper, Barbara, committee member; Dickman Portz, Jennifer, committee member (Colorado State University. Libraries, 2018)
Participation in occupation is essential for human health and well-being. While therapeutic activities and techniques can be useful, they do not contribute to survival, health, or well-being in the powerful way that occupation does; therefore, it is important to understand how occupation develops. While there has been some research on how children develop occupations, little research has been conducted to understand the ways in which adults develop new occupations or the ways in which activities transform into occupations. This study explored the development of one potential occupation, yoga, among a group of eight people participating in a study of yoga for chronic pain. Interviews and a focus group were used to explore the process, supports, and barriers of yoga developing as an occupation. Several results were most significant. First, the process of yoga developing as an occupation varied among participants and progressed non-sequentially. The process included the elements of initial reluctance, consistency, meaning increase, transfer, and identity. Second, the process of yoga developing as an occupation was supported by several factors: the yoga classes being adapted and accessible to participant abilities; the class transforming into a socially meaningful group experience; and yoga becoming more meaningful as participants recognized their personal benefits.
Keywords: chronic pain; yoga; occupational science; adult development of occupation